2020
DOI: 10.1016/j.chempr.2020.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective C–H Benzylation of Alkanes with N-Triftosylhydrazones Leading to Alkyl Aromatics

Abstract: Alkanes are an abundant and valuable resource for transformation into value-added fine chemicals.However, selective functionalization of specific C(sp 3 )-H bonds in alkanes is a significant challenge, particularly for alkyl-alkyl bond formation, due to the small differences in reactivity between the various C(sp 3 )-H bonds in alkanes and their intrinsic inertness. Herein, we report a silver-catalyzed site-selective C(sp 3 )-H benzylation of simple alkanes using N-triftosylhydrazones as a convenient carbene p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 71 publications
1
50
0
1
Order By: Relevance
“…In addition to indole-3-carbinols, indole-2-carbinols could also be employed without difficulty in this transformation, affording the corresponding products featuring an enamine motif (34)(35)(36)(37)(38), which are difficult to access with conventional methods 56,57 . Regarding the scope of N-triftosylhydrazones, an array of substrates reacted smoothly with indole-3carbinol, affording the corresponding products (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56) in high yield. Functional groups such as methyl (39,40), tert-butyl (41), methoxy (42,53), trifluoromethoxy (43), phenyl (44), halogen (45-48, 51, 52), trifluoromethyl (49), and vinyl (50) were well tolerated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to indole-3-carbinols, indole-2-carbinols could also be employed without difficulty in this transformation, affording the corresponding products featuring an enamine motif (34)(35)(36)(37)(38), which are difficult to access with conventional methods 56,57 . Regarding the scope of N-triftosylhydrazones, an array of substrates reacted smoothly with indole-3carbinol, affording the corresponding products (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56) in high yield. Functional groups such as methyl (39,40), tert-butyl (41), methoxy (42,53), trifluoromethoxy (43), phenyl (44), halogen (45-48, 51, 52), trifluoromethyl (49), and vinyl (50) were well tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…1c, up). Through the formation of N-sulfonylhydrazones, fluoroalkyl ketones have recently become versatile coupling partners, especially as a source of fluoroalkyl carbene in a range of C-C bond-forming reactions [39][40][41][42][43][44][45][46][47] . We envisaged that an intramolecular rearrangement strategy could provide an advantageous route for the efficient carbodefluorination of trifluoromethyl ketones, i.e., the formation of an oxonium ylide intermediate by nucleophilic addition of β,γ-unsaturated alcohols to a fluoroalkyl metal carbene might enable a sequential C-F bond cleavage / C-C bond formation through the Claisen rearrangement of an in situ generated difluorovinyl ether intermediate (Fig.…”
Section: Fig 1 Background and Motivation For Carbodefluorination Of C...mentioning
confidence: 99%
“…2015 年, 刘统信和张贵生课题组 [41] [45] . 近期, 我们课题组 [46] [47] 实现了铑卡宾对环丁醇体系 C-C 键的选择性插入, 底物内在的张力是实现上述 C-C 键选择性活化的关键因素. 2018 年, 毕锡和课题 组 [48] [51] 于 1968 年报道, 1981 年 Doyle 等 [52] 对该 反应进行了改进, 是构建新型 C-C 键和 C(sp 3 )-S 键的 重要方法, 因此多年以来, 该反应一直备受化学工作者 关注 [53] .…”
Section: [3+2]环加成反应unclassified
“…For reactions between donor diazo compounds and unactivated diarylalkenes, no efficient method had been available until we reported the silver-catalyzed cyclopropanation of alkenesb yu sing N-nosylhydrazones as diazo surrogates. [15][16][17][18][19][20][21] Our previous experiments have shown that, compared with other transition-metal (copper,g old, ruthenium,p alladium) salts, which are often used as carbenet ransfer catalysts, only silver salts showh igh catalytic activity (Scheme2). [15] However, the detailed mechanismo ft he Ag-catalyzed cyclopropanation of alkenes by sulfonyl hydrazones remains unknown, and the reason for the high catalytic activity of silver salts is still unclear.T hus,w ec arried out DFTcalculations to elucidate 1) the mechanism of the Ag-catalyzed cyclopropanation of alkenes by sulfonyl hydrazones, 2) the origin of the high catalytic activity of silver salts, and 3) the main reason for the lowe fficiency of cyclopropanation catalyzed by CuOAc andP dCl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…SbF 6 − has strong polarization and can be used as a weak ligand, which can disperse electrons and improve the reactivity of the silver carbene. For reactions between donor diazo compounds and unactivated diarylalkenes, no efficient method had been available until we reported the silver‐catalyzed cyclopropanation of alkenes by using N ‐nosylhydrazones as diazo surrogates [15–21] …”
Section: Introductionmentioning
confidence: 99%